Codonopsis pilosula oligosaccharides modulate the gut microbiota and change serum metabolomic profiles in high-fat diet-induced obese mice. Issue 15 (11th July 2022) - Bai, Ruibin; Cui, Fang; Li, Wen; Wang, Yanping; Wang, Zixia; Gao, Yingrui; Wang, Nan; Xu, Qiaohong; Hu, Fangdi; Zhang, Yan
Abstract : Codonopsis pilosula oligosaccharides (CPOs) showed promising anti-obesity effects in HFD-induced obese mice. Abstract : Obesity has become a major health problem worldwide, linked to gut microbiota imbalance and chronic inflammation. This study aims to evaluate whether Codonopsis pilosula oligosaccharides (CPOs) can alleviate obesity and related metabolic complications in high-fat diet (HFD) induced obese mice. Male C57BL/6J mice were fed with a HFD for 16 weeks and treated daily with CPOs (500 mg kg −1 ). CPO supplementation decreased body weight and fat accumulation and improved glucose tolerance in HFD-fed mice. CPOs also reversed the effects of the HFD on inflammatory markers and improved macrophage infiltration. The results of gut microbiota analysis showed that CPOs could also regulate gut microbiota composition, significantly increasing the abundance of the beneficial bacteria Muribaculaceae spp., Alistipes and Clostridium and decreasing the abundance of the harmful bacteria Rikenella, Enterobacteriaceae spp., Collinsella and Megasphaera in HFD mice. Based on serum non-targeted metabolomics analysis, 20 key metabolites responding to CPO treatment were identified, and their biological functions were mainly related to tryptophan and bile acid metabolism. The results demonstrate that CPO supplementation can ameliorate HFD-induced obesity and obesity-related metabolic disorders. It can be used as a novel gut microbiota modulator to prevent HFD-induced gut dysbiosis.